RESTRUCTURING POLICY FOR PROBLEMATIC MURABAHAH FINANCING FOR MSME CUSTOMERS DUE TO THE 2019 CORONAVIRUS DISEASE (COVID-19) PANDEMIC - Vera Hardianti (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2022)
The Covid-19 pandemic has a direct or indirect impact on MSME customers which makes it difficult for them to fulfill their obligations to Shariah Banks which of course results in problematic financing. Non-performing financing has the potential to disrupt banking performance and financial system stability, which can affect economic growth. The problematic formulation that has the potential to disrupt banking performance and financial system stability that will be discussed in this study is about sharia bank policies towards problematic murabahah financing for MSME customers affected by Covid-19. The research approach used is a statutory approach and a conceptual approach. The results of this study are that Shariah Banks in providing murabahah financing restructuring to customers who have difficulty fulfilling their obligations to Shariah Banks due to their business being affected by Covid-19. The policy is completely left to Shariah Banks and is highly dependent on the results of the identification of Shariah Banks on the financial performance of customers or an assessment of business prospects and the capacity to pay for MSMEs affected by Covid-19.